Defense Against Violence Directed at a Third Party: A Comparative Study of Islamic Criminal Law and Indonesian Criminal Law - Holik Holik; Abu Yazid Adnan Quthny; Abd Hannan (Rechtsvinding, 2026)
Defense of a third party is an act carried out by an individual to protect another person from unlawful attacks or threats. In practice, such actions often create legal dilemmas because they may fulfill the elements of a criminal offense despite being intended to protect victims. This study aims to analyze the concept of third-party defense in Indonesian criminal law and Islamic criminal law, identify their similarities and differences, and examine their implications for law enforcement in Indonesia. This research employs a normative juridical method with statutory, conceptual, and comparative approaches. Data were collected through library research involving legislation, legal literature, scientific journals, and Islamic legal sources such as the Qur’an, Hadith, and scholars’ opinions. The findings indicate that Indonesian criminal law recognizes defense of others through the concept of noodweer, emphasizing objective elements such as unlawful attacks, necessity, and proportionality. Islamic criminal law recognizes third-party defense through the principles of hifz al-nafs and maqashid al-syari’ah by considering intention, public benefit, and prevention of harm. The similarity lies in the recognition of the right to defend others, while the difference lies in their philosophical foundations and assessment parameters. This study contributes a conceptual framework for third-party defense that integrates legal certainty, justice, and social benefit.